A cross-sectional study on the prevalence of hypodontia in UPCD postgraduate orthodontic patients and the frequency distribution of their congenitally missing teeth - Dehesa, Diane G.
Foreign studies have documented several cases of hypodontia or congenitally missing teeth dating as early as 1850's. The studies that have been conducted concerning the prevalence, etiology, treatment, frequency distribution of the missing teeth, and sex predilection of hypodontia have variable results. At present, no local studies have been documented regarding the prevalence of hypodontia other than third molars among Filipinos. It was then the main objective of the study to determine the prevalence of hypodontia other than third molars in UPCD Postgraduate Orthodontic Patients. The study undertaken was a cross-sectional study which examined 346 charts of UPCD Postgraduate Orthodontic Patients, 275 of which belonged to the age group of 12-25, male and female with permanent dentition. Examination of the patients' charts particularly panoramic radiograph, intraoral photograph and case history was conducted. The study showed that 9.8% of the subjects have hypodontia and it is more prevalent in females than in males. The most frequently absent teeth are mandibular lateral incisors and maxillary lateral incisors, having the same frequency, followed by mandibular central incisors, maxillary cuspids, and maxillary first bicuspids. Results of the present study vary from those of the foreign studies. There was little indication that systemic diseases influence the development of hypodontia. It would be better if a more detailed medical and family history will be recorded in the patient's chart to help determine the influence of heredity, systemic diseases and other medical condition on the development of hypodontia.